Associations among tooth loss, systemic inflammation and antibody titers to periodontal pathogens in Japanese patients with cardiovascular disease. (15th November 2017) - Aoyama, N.; Suzuki, J.‐I.; Kobayashi, N.; Hanatani, T.; Ashigaki, N.; Yoshida, A.; Shiheido, Y.; Sato, H.; Minabe, M.; Izumi, Y.; Isobe, M.
Abstract : Background and Objective: It is well known that there is a strong relationship between periodontitis and cardiovascular disease (CVD). Tooth loss reflects an end‐stage condition of oral diseases, such as periodontitis. Infection with specific periodontal pathogens is known as a possible factor that influences development of CVD. The aim of this study was to assess the relationship between the number of residual teeth and systemic inflammatory conditions in patients with CVD. Material and Methods: We divided 364 patients with CVD into four groups, according to the number of residual teeth: (i) ≥20 teeth; (ii) 10‐19 teeth; (iii) 1‐9 teeth; and (iv) edentulous. We recorded medical history, blood data and periodontal conditions. Serum samples were obtained and their IgG titers against three major periodontal pathogens were measured. Results: Smoking rate and the prevalence of diabetes mellitus were higher in edentulous patients and in subjects with a few teeth compared with patients with many teeth. The levels of C‐reactive protein were higher in patients with 1‐9 teeth than in those with 10‐19 teeth and with ≥20 teeth. The level of Porphyromonas gingivalis IgG in the group with 10‐19 teeth was statistically higher than that in the group with ≥20 teeth. The level of P. gingivalis IgG in the edentulous group tended to be lower than that in the other groups. Conclusion: The patients with 1‐9 teeth had the highest level of C‐reactive protein among the four groups, and the patients with 10‐19 teeth had the highest level of IgG to periodontal bacteria. We conclude that the number of remaining teeth may be used to estimate the severity of systemic inflammation in patients with CVD.